2020
DOI: 10.1016/j.ctrv.2020.102090
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DNA damage response for patients with lymphoma: Preclinical and clinical evidences

Abstract: The DNA damage response (DDR) is a well-coordinated cellular network activated by DNA damage. The unravelling of the key players in DDR, their specific inactivation in different tumor types and the synthesis of specific chemical inhibitors of DDR represent a new hot topic in cancer therapy. In this article, we will review the importance of DDR in lymphoma development and how this can be exploited therapeutically. Specifically, we will focus on CHK1, WEE1, ATR, DNA-PK and PARP inhibitors, for which preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 203 publications
(288 reference statements)
0
36
0
Order By: Relevance
“…Many studies have shown that simultaneously targeting PARPs and cell cycle checkpoints (ATR, CHK1, and WEE1) can overcome the resistance caused by restored replication fork stabilization. 589,590 A phase II study of olaparib plus ATR/WEE1 inhibitor vs. olaparib monotherapy is currently underway in TNBC patients (NCT04191135). 591 Moreover, it should be noted that combination therapy may also increase the risk of side effects.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…Many studies have shown that simultaneously targeting PARPs and cell cycle checkpoints (ATR, CHK1, and WEE1) can overcome the resistance caused by restored replication fork stabilization. 589,590 A phase II study of olaparib plus ATR/WEE1 inhibitor vs. olaparib monotherapy is currently underway in TNBC patients (NCT04191135). 591 Moreover, it should be noted that combination therapy may also increase the risk of side effects.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…The DDR comprises a complex network of proteins that sense specific types of DNA lesions and respond to them by activating the necessary DNA repair mechanisms, and timely regulating cell cycle progression through checkpoint activation, with the final aim of repairing the damage, or if the damage is too extensive to induce cell death ( 25 , 26 ). It is hardly surprising, that proteins like PLK1 involved in the surveillance mechanisms of cell cycle progression are also involved in the DDR, due to the close interactions among these mechanisms.…”
Section: Plk1 and Its Role In Genomic Stabilitymentioning
confidence: 99%
“…In particular, such strategy is appealing in B-cell lymphomas, as during maturation and antibodies production, B cells experience somatic hypermutation and V(D)J recombination, which expose cells to high levels of DNA damage. For this, in recent years, several inhibitors of DDR proteins—including ATR, DNA-PK, PARP, Chk1, and WEE1, administered alone and in combination with other agents—have been preclinically tested [ 39 ]. Consistently, ATR inhibitors have shown strong cytotoxic and in vivo antitumor activity in mantle cell lymphomas (MCL) and DLBCL, regardless of their TP53 , MYC , and ATM mutation status [ 40 ].…”
Section: Discussionmentioning
confidence: 99%